Congenital malformations of the fetus: Clinical case from practice - Gulnar Tortayeva; Anara Shakirova (National Scientific Medical Center, 2017)
The article describes the case of congenital malformations of the fetus, caused by amniotic constriction, as a consequence of defective formation of aminoin (internal germinal septum). In the literature, these defects are most often described as a syndrome of amniotic constrictions. This case is presented in connection with a rare occurrence of the syndrome, characterized by the clinical heterogeneity of the syndrome characterized by clinical heterogeneity - more often it is the defects of the limbs, face, skull and brain.